KOTAK SAMPAH PINTAR BERBASIS MIKROKONTROLER - Dimas Febrian; Ade Winarni; Saharudin Saharudin (LPPM STMIK BANDUNG, 2019)
One of human needs is a comfortable environment. A comfortable living environment can be created if humans maintain cleanliness, so it is very important to raise awareness of protecting the environment by disposing of trash in its place. Trash cans are things that we usually encounter around us, but the existence of trash can is not always good. Lack of community interest in littering, overloading bins is a problem that we often encounter in trash bins. Dirty trash cans make people reluctant to open and throw garbage into it.The method used to build a microcontroller-based smart trash system uses a spiral method that consists of sequential stages, namely, (1) Planning or planning, (2) Risk Analysis or risk analysis, (3) Engineering or engineering , (4) Evaluation Stage. The design of this system uses several hardware modules consisting of an ATMega 328 microcontroller, HC-SR04, Servo Motor, Sim800l, HC-05, Stepdown, LED, and an android software editor namely, Mitapp Inventor 2 to create a trash can controller application.On the results of distance measurements by ultrasonic sensors can read a distance of 3-400 cm with an angle of less than 15 degrees, the condition of the specified distance is less than 4 cm on the opening and notification sensor and a maximum distance of 10 m for the Bluetooth module to connect to the smartphone used to control the trash. The main process of input data by the module used will be processed on the ATMega 328 microcontroller. Overall this system can work well to be an attraction so that users can improve the hygiene and cleanliness of the environment.